Electrocardiographic Findings in Accessory Right Precordial Leads in Adults and Seniors with Notched S Waves in Lead V(1)—A Preliminary Study - Zhong‐qun, Zhan (Ann Noninvasive Electrocardiol, 2013)
BACKGROUND: Atypical right bundle branch block (RBBB) may present with an rS pattern and notched S wave in lead V(1). The notched S wave may represent slowed conduction or delayed activation of the right ventricular conduction system or ventricular myocardium. METHODS: We retrospectively analyzed the QRS patterns in accessory right precordial leads (from V(3)R to V(5)R) in 15 adults/senior individuals with notched S wave in lead V(1). RESULTS: In the right accessory precordial leads, 13 showed triphasic QRS pattern with final R′ wave in their QRS complexes. This QRS pattern in association with notched S wave in lead V(1) is suggestive of the presence of RBBB (incomplete or complete). CONCLUSIONS: A notched S wave in lead V(1) and in the right precordial accessory leads associated with a final R′ wave suggests the possibility of concealed RBBB (incomplete or complete).